1973
DOI: 10.1088/0022-3727/6/11/312
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron and backscattering measurements for polycrystalline copper with a spherical retarding-field analyser

Abstract: A full spherical retarding-field energy analyser with three grids was made to measure the total secondary electron yield σ, the backscattering coefficient η, and the secondary electron spectrum N(E) as a function of angle of incidence and primary energy in UHV. The instrumental effects of the grid meshes in the measurement of N(E) were minimized by using the sample-bias-modulation technique. The values of σ and η for polycrystalline copper were found to be rather higher than previously published values. The N(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 16 publications
5
40
0
Order By: Relevance
“…If the initial SE is too close to the surface, then perhaps SE cascade will not be as strong as a cascade that had been initiated at a slightly greater depth. This is in accord with the work of Koshikawa and Shimizu (1973) who found that the SE emission does not follow a simple exponential decay law for SE escaping from the surface. In addition, the effective atomic number Z eff that the PE feels from an atom in the sample will reduce as the primary energy reduces, thus reducing the capacity for generating SEs.…”
Section: Discussionsupporting
confidence: 92%
“…If the initial SE is too close to the surface, then perhaps SE cascade will not be as strong as a cascade that had been initiated at a slightly greater depth. This is in accord with the work of Koshikawa and Shimizu (1973) who found that the SE emission does not follow a simple exponential decay law for SE escaping from the surface. In addition, the effective atomic number Z eff that the PE feels from an atom in the sample will reduce as the primary energy reduces, thus reducing the capacity for generating SEs.…”
Section: Discussionsupporting
confidence: 92%
“…Then the q($) curves show a lower increase with increasing $ than expected from (26), which is more pronounced for 1 keV than 10 keV. Similar results are reported by Darlington and Cosslett (1972), Fitting and Technow (1983), and Koshikawa and Shimizu (1973). Carlo simulations (Fig.…”
Section: Dependence Of Backscattering On Surface Tiltsupporting
confidence: 86%
“…Histogram is the present Monte Carlo-calculated result (solid line). Experimental curves measured with hemispheric analyzers are: (dashed line) Koshikawa and Shimizu (1973), (thin solid line) Pillon quoted by Ganachaud (1977), (thin dashed line) Goto et al (1975).…”
Section: Monte Carlo Calculation For Scanning Electron Microscopy Yiementioning
confidence: 97%
“…Solid line is derived from EN(E) spectrum experimentally measured with a CMA (Goto et al 1994) and data points represent Monte Carlo-calculated result for: (a) CMA solid angles for detection, (b) hemispheric solid angles. (Koshikawa and Shimizu 1973) and dashed lines (Goto et al 1975) (Bindi et al 1980) are experimental data. Hatched region represents the variation of experimental curves for δ using experimental data for δ max and E p max and an empirical equation δ(E p ) (Seiler 1983).…”
Section: Fig 15mentioning
confidence: 99%